School Choice and the Housing Market - Grigoryan, Aram (Review of Economic Studies, 2026)
Abstract I develop a unified theoretical framework with schools and residential choices to study the welfare consequences of public schools’ switching from the traditional neighbourhood assignment to the deferred acceptance mechanism. I find that when families receive higher priorities at neighbourhood schools, the deferred acceptance mechanism creates higher aggregate or utilitarian welfare than neighbourhood assignment. Under a common school ranking assumption, I also show that the deferred acceptance creates higher aggregate welfare with neighbourhood priorities than without them.